The Effect of Self-Efficacy on College Students’ Physical Fitness Test Scores - Huang, Shiying (Transactions on Social Science, Education and Humanities Research, 2024)
The 8th National Student Physique and Health Survey indicates a slight improvement of 0.2% in the achievement of college students in meeting the standard of excellent physical health. To address the lack of research in this area, a survey was conducted among 1300 students from various grades at Jingdezhen Ceramic University. The study delves into the complex link between college students’ self-efficacy and their scores on physical fitness tests, with the goal of offering deep insights to enhance the overall health and physical fitness of this group. The findings reveal a strong positive relationship between levels of self-efficacy and scores on physical fitness tests, underscoring self-efficacy as a key predictor of students’ performance on these tests. Moreover, gender differences in self-efficacy dimensions for males were examined, showing that while there were no significant variations between males and females in each dimension, males had higher mean scores in self-efficacy than females. The results highlight the significance of boosting self-efficacy, regulating emotions, diversifying sports activities, creating a healthy academic setting, fostering positive self-assessment, and addressing gender-specific requirements in enhancing the physical health of college students.